STREPTOCOCCAL TONSILLITIS IN CHILDREN - M. M. Polunin; L. S. Titarova; T. A. Polunina (Педиатрическая фармакология)
The problem of acute tonsillitis retains its relevance over the past few years. Its most frequent causative agent is the ß-hemolytic streptococcus group A. This article covers the clinical presentation of the disease and its differential diagnosis as well as modern methods of diagnosing and treating the disease. The therapy of acute tonsillitis is based on a complex approach, which allows to increase its effectiveness considerably. It is offered to use local-effect antibacterial drugs alongside the systemic antibacterial therapy. There are recommendations on the usage of pastilles for local antibacterial treatment, which allow to decrease the pain intensity during streptococcal tonsillitis and to decrease the probability of complications.